Daphnia magna and Xenopus laevis as in vivo models to probe toxicity and uptake of quantum dots functionalized with gH625 - Galdiero E (Dove Medical Press, 2017)
Emilia Galdiero,1 Annarita Falanga,2 Antonietta Siciliano,1 Valeria Maselli,1 Marco Guida,1 Rosa Carotenuto,1 Margherita Tussellino,1 Lucia Lombardi,3 Giovanna Benvenuto,4 Stefania Galdiero2 1Department of Biology, 2Department of Pharmacy and CiRPEB, University of Naples Federico II, 3Department of Experimental Medicine, Second University of Naples, 4Stazione Zoologica Anton Dohrn, Villa Comunale, Napoli, Italy Abstract: The use of quantum dots (QDs) for nanomedicine is hampered by their potential toxicologic effects and difficulties with delivery into the cell interior. We accomplished an in vivo study exploiting Daphnia magna and Xenopus laevis to evaluate both toxicity and uptake of QDs coated with the membranotropic peptide gH625 derived from the glycoprotein H of herpes simplex virus and widely used for drug delivery studies. We evaluated and compared the effects of QDs and gH625-QDs on the survival, uptake, induction of several responsive pathways and genotoxicity in D. magna, and we found that QDs coating plays a key role. Moreover, studies on X. laevis embryos allowed to better understand their cell/tissue localization and delivery efficacy. X. laevis embryos raised in Frog Embryo Teratogenesis Assay-Xenopus containing QDs or gH625-QDs showed that both nanoparticles localized in the gills, lung and intestine, but they showed different distributions, indicating that the uptake of gH625-QDs was enhanced; the functionalized QDs had a significantly lower toxic effect on embryos’ survival and phenotypes. We observed that D. magna and X. laevis are useful in vivo models for toxicity and drug delivery studies. Keywords: membranotropic peptide, delivery, blood–brain barrier, nanoparticles, genotoxicity